Time integral of synaptic conductance. - Gardner, D (1980)
1. Inhibitory post-synaptic currents (i.p.s.c.s) were recorded under voltage clamp from neurones of Aplysia buccal ganglia. 2. The synaptic charge, Q, transferred by each i.p.s.c. was calculated as the time integral of the synaptic current, approximated by numerical integration. For typical i.p.s.c.s recorded at or near resting potential, Q = -100 to -500 pC. The majority of the charge is transferred during the interval between the peak and a time one time constant later. 3. In order to characterize an alternative measurement of synaptic efficacy, the slope of the Q vs. membrane potential curve was calculated and defined as the time integral of conductance, b. Values of b ranged from 2.6 to 51 pC/mV, averaging 14 pC/mV. For i.p.s.c.s recorded in thirty-one cells at room temperature, b was well correlated with Gpeak, the peak synaptic conductance (r = 0.86). 4. In most synapses, the time integral of conductance, which incorporates both amplitude and duration, may be a more revealing measure of synaptic efficacy than peak conductance. 5. Size of synaptic response was determined as a function of temperature, T. While Gpeak decreases with decreasing temperature over the range 9-22 degrees C, b peaks at 12-18 degrees C and decreases at higher and lower values of T. The data permit the speculation that lengthening average channel lifetime, and therefore time constant of decay, with decreasing temperature, may have adaptive significance in maintaining synaptic efficacy.